A dimensão subjetiva da educação alimentar e nutricional escolar: construindo subsídios para a formação docente - Silva, Maria de Fátima Gomes da (2019)
The objective of this thesis is to apprehend the subjective dimension of Food and Nutritional Education (FNE) in local public schools of Elementary Education and, simultaneously, building subsidies to teacher training on the subject. The dichotomy between feeding/ nutrition, subject/object present in the field of Nutrition Science and in school FNE, is an important indicator for the necessary articulation between the field of Nutrition and the Human and Social Sciences. As a theoretical-methodological foundation, Thesis adopts Historical and Dialectical Materialism and Socio-Historical Psychology, which brings with it the criticism possibility due to his theoretical, methodological and epistemological foundations. The research has involved two groups. The first group is formed by nineteen teachers from three different schools from the city of Diamantina (MG); and the second one is formed by nine teachers of a school from the city of São Paulo (SP). The data production of the first group occurred during eight meetings, coordinated by seven researchers; and data from the second one, during nine meetings, coordinated by two researchers. For data production, a strategy called “Research and Training” was adopted, which has as some of its principles the collaboration and critical reflection about reality in the search of its transformation. The meetings were video recorded, transcribed, and later analyzed and interpreted by the procedure called “Nuclei of Meaning”, which has as purpose apprehend the meaning of the subjects beyond appearances. Four articulated Nuclei of Meaning were built: “the meaning and resignification of FNE: the importance of the discussion and construction of concepts related to Food and Nutrition in teacher training”; "FNE and the possibilities of curricular integration towards interdisciplinarity"; "The class ideology mediated in schools: conceptions of food, feeding and deficiencies as mediators"; "The ambiguous understanding of the nutritionist's performance in schools: present only to legitimize school feeding?". The first nucleus, affirms that the "Research and Training" strategy, enabled teachers and researchers to act in a collaborative way, articulating in a critical and reflexive way theory and practice (praxis), making possible the development of new concepts about food and nutrition. Another synthesis, shows the possibility of incorporating the FNE transversally to the school curriculum, towards interdisciplinarity. The third nucleus warns that class ideology, present in the school environment, can become an obstacle to the school that has as commitment a critical action with a view to the reality. The last nucleus warns about the necessary understanding the absence of the nutritionist in schools. The built syntheses contribute as subsidies for teacher training in FNE by showing that, based on the teachers' meanings, important FNE elements were found in the schools studied, evidencing their multiple determinations, including the dialectical relationship between objectivity and subjectivity and, therefore, the Subjective Dimension that the FNE constitutes in schools